Teaching Progress: A Critique of the Grand Narrative of Human Rights as Pedagogy for Marginalized Students - Linde, Robyn; Arthur, Mikaila Mariel Lemonik (Radical Teacher, 2015)
With the adoption of the Universal Declaration of Human Rights in 1948, education about human rights became an important focus of the new human rights regime and a core method of spreading its values throughout the world. This story of human rights is consistently presented as a progressive teleology that contextualizes the expansion of rights within a larger grand narrative of liberalization, emancipation, and social justice. This paper examines the disjuncture between the grand narrative on international movements for human rights and social justice and the lived experiences of marginalized students in urban environments in the United States. Drawing on our experience as professors who teach human rights, social justice, and social movements courses at an urban, four-year college in Providence, R.I., with a student body which includes large populations of students who are of color, first-generation, economically disadvantaged, and nontraditional in other ways, we explore the relevance and impact of these grand narratives for the lives of our students and their sense of agency. In particular, we advocate for a critical and transformational approach to human rights pedagogy to counter and overcome the pervasive individualization that undergirds the grand narrative of human rights. We argue that a critical (and radical) human rights pedagogy must evaluate the position of the individual in modern life if liberation through human rights law and activism is to be possible.